Castro de Monte Mozinho: Lucernas - Esteves, Andreia Filipa Campos; Nunes, Flávia Maria Magalhães (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
The fieldwork carried out between 1974 and 1998 at Castro de Monte Mozinho (Penafiel) yielded a significant number of Roman oil lamps (high and low-imperial) and of production of indigenous tradition. The collection indicates a clear predominance of oil lamps originating from central-Italy workshops, Hispanic, but also of local (Castro de Monte Mozinho) and regional productions. Of the latter, many of them refer to a Bracara Augusta production, as that city was an important producer and oil lamps distributor known at conventus. The focus tends to be mainly on the regional market, as shown in Monte Mozinho.